2015
DOI: 10.1007/s00259-015-3049-y
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel lymph node biopsy in oral and oropharyngeal squamous cell carcinoma: current status and unresolved challenges

Abstract: Because imaging with ultrasound, computed tomography, magnetic resonance imaging or positron emission tomography is unreliable for preoperative lymph node staging of early-stage oral and oropharyngeal squamous cell carcinoma (OSCC), elective neck dissection has been typically performed. The targeted sampling of sentinel lymph nodes (SLN) identified by lymphoscintigraphy and detected by gamma probe has become an effective alternative for the selection of patients for regional nodal resection. With careful consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 102 publications
0
23
0
Order By: Relevance
“…Good diagnostic accuracy in identification of these metastases by SNLB have been demonstrated by multiple long-term experience studies. 53 Studies have also demonstrated that SLNB can decrease the rate of occult metastases to lymph nodes from 40% to 8%. 54 Alvarez Am ezaga et al 55 performed a meta-analysis of available data that demonstrated sensitivity and specificity of 93% and 100%, respectively.…”
Section: What About the Sentinel Lymph Node Biopsy?mentioning
confidence: 99%
See 3 more Smart Citations
“…Good diagnostic accuracy in identification of these metastases by SNLB have been demonstrated by multiple long-term experience studies. 53 Studies have also demonstrated that SLNB can decrease the rate of occult metastases to lymph nodes from 40% to 8%. 54 Alvarez Am ezaga et al 55 performed a meta-analysis of available data that demonstrated sensitivity and specificity of 93% and 100%, respectively.…”
Section: What About the Sentinel Lymph Node Biopsy?mentioning
confidence: 99%
“…A positive SLNB should be followed by a neck dissection. Good diagnostic accuracy in identification of these metastases by SNLB have been demonstrated by multiple long‐term experience studies . Studies have also demonstrated that SLNB can decrease the rate of occult metastases to lymph nodes from 40% to 8% .…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…This method has become the standard‐of‐care in many tertiary referral centers, mostly in Europe . However, it can be resource‐ and time‐consuming …”
Section: Introductionmentioning
confidence: 99%